Function, phenotype and development of human CD161+CD8 T cells - Walker, LJ (2012)
Tc17 cells and the semi-invariant human mucosal associated invariant T (MAIT) cells are important CD8+ tissue-homing cell populations. Both are characterized by high expression of CD161 (++) and type-17 differentiation, yet their origins and relationships remain poorly defined. By transcriptional and functional analyses it is demonstrated that a pool of polyclonal, pre-committed type-17 CD161++CD8αβ+ T cells exists in cord blood, from which a prominent MAIT cell (TCR Vα7.2+/Vβ2 or 13.2) population emerges post-natally. During this expansion, CD8αα T-cells appear exclusively within CD161++CD8+/MAIT subset, sharing cytokine production (IL17, IL-22 and IFN-γ), chemokine-receptor expression (CCR2, CCR6 and CXCR6), TCR-usage and transcriptional profiles with their CD161++CD8αβ+ counterparts. These data demonstrate the origin and differentiation pathway of MAIT cells from a naïve type-17 pre-committed CD161++CD8+ T cell pool and the distinct phenotype and function of CD8αα cells in man. The CD161++CD8αβ and CD8αα T cell subsets are reduced in the peripheral circulation in chronic hepatitis B and C and are enriched in the liver in chronic hepatitis C. Their potential role in immunity to chronic viral hepatitis B and C is demonstrated by their expression of activation/exhaustion markers CD69, CD25, HLA-DR and PD-1. In addition a substantial distinct CD161-CD8βlow population is demonstrated in chronic hepatitis B, co-characterised by a CD28low, HLA-DRhigh phenotype and high expression of IFN-γ, with important implications for the development of immunotherapy and vaccination.